795. Review of Treatment of Latent Tuberculosis Infection at VA Portland Healthcare System. (26th November 2018) - Xu, Teena; Forrest, Graeme N
Abstract: Background: Treatment of latent tuberculosis infection (LTBI) is important for tuberculosis elimination in low-incidence countries. Currently, the VA Portland Health Care System (VAPORHCS) offers both 3HP (12-dose rifapentine plus isoniazid directly observed therapy (DOT)) and 9H (9-month daily isoniazid) for treatment of LTBI. Majority of veterans are treated with 9H despite increasing evidence showing higher rates of completion with 3HP. We reviewed the rates of completion and adverse events (AE) between veterans treated with 3HP and 9H. Methods: We performed a retrospective chart review on all patients within the VAPORHCS who initiated LTBI treatment with 9H or 3HP between January 2011 and December 2016. LTBI was diagnosed through tuberculin skin testing or interferon-γ release assay. 9H treatment was self administered while 3HP was under DOT. Collected data included demographics, co-morbid conditions, immunosuppression, treatment completion, and AE. Treatment completion was determined through chart documentation. Results: A total of 93 patients were treated for LTBI. Most patients were white (71%) and male (86%). The median age was 57 years old. Seventy-two patients (77%) were treated with 9H, and 21 (23%) were treated with 3HP. The overall completion rate was 86%. Completion rates between 9H (91%) and 3HP (86%) were not significantly different ( P = 0.46). Twenty-three patients (31.9%) on 9H and six patients (28.6%) on 3HP were on chronic immunosuppression with TNF inhibitors and/or corticosteroids ( P = 0.78) with an overall completion rate of 86%. Nine patients (13%) on 9H and two patients (10%) on 3HP had HIV ( P = 0.95). Overall rates of AEs were similar between the groups (4%, 14%, P = 0.11), including hepatotoxicity (2%, 0%, P = 0.57) and neurotoxicity (4%, 5%, P = 0.94). Conclusion: The overall treatment completion rates were high and statistically similar between 9H and 3HP groups, even with immunosuppressive therapy. There were no significant differences in rates of adverse events. While the majority of patients were treated with 9H, these results suggest an opportunity for more use of the 3HP, possibly without the need for DOT regimen going forward. Disclosures: All authors: No reported disclosures.